Metaphorization: World View or World Creation? - Kanišauskaitė-Medonienė, Odeta (Kalbotyra, 2002)
Taking up the perspective of language philosophy and cognitive semantics, the paper analyses various types or reconceptualization via metaphorization. The need to investigate metaphorical reconceptualization of reality arises after a close look at contemporary cognitive views on metaphor where a very manifold phenomenon is implied under the same term ‘metaphor’ - a tool of conceptualization as well as reconceptualization of human experience, a tool in the creation of fictionality of poetic texts, and the phenomenon that changes the states of affairs in the actual world. Schema theory is applied to show that metaphorization may act as schema connection, reinforcement, enrichment and refreshment, and that reconceptualization of the reality is a scalar category ranging from the most conventional world view to the creation of new insights and worlds.